CHILDREN’S SOCIAL SKILLS THROUGH TRADITIONAL SPORT GAMES IN PRIMARY SCHOOLS - Johan Irmansyah; Ria Lumintuarso; FX. Sugiyanto; Pamuji Sukoco (Jurnal Cakrawala Pendidikan, 2020)
Traditional society still perceives that physical education is ineffective in shaping children’s character and that physical education is still considered as only a playing activity without having significant effects to the development of children’s social skill. This research aims to help children shape their social skills through the traditional games provided by physical education teachers with their comprehensive playing activities. The method used in this research was a qualitative approach, by doing some observations and unstructured interviews to teachers and students. The format of the game used in this research was the modification of traditional games called ‘Gobak Sodor’ which is adapted to the multilateral development of children and the theory of sports education. The result of observation and interview shows that the modified traditional games ‘Gobak Sodor’ can help children to shape their social skills, such as personal and social responsibility, teamwork, communication and the care of each other in the game. It can be concluded that the social skills of children can not be created instantly. It requires time and continuous learning process. One of the approaches which can be used in forming children’s social skills is modified traditional sport games ‘Gobak Sodor’.